Namık Kemal’in mektuplarında “şiir, tiyatro ve gazete” üzerine tenkitler - Şahin, Veysel (My University, 2010)
Namık Kemal’in özel mektupları, Tanzimat devri ve fikir hayatının zengin kaynağı olup edebiyat, sanat ve kültür tarihimiz açısından önemli bir tarihi belge niteliği taşır. Sanatçı, dönemindeki gençlere mektup yazarak onların eserlerini tenkit eder. Namık Kemal’in özel mektuplarında edebî türler hakkındaki tenkitlerini; şiir, tiyatro, gazete başlığı altında ele alarak, onun bu edebî türlerin gelişmesindeki katkılarını ortaya koyduk.

Namık Kemal’s private letters are a rich source of the Tanzimat Period and ıts thought life and are of historical documents with respect to our history of literature and culture. In this study Namık Kemal’s critics on the literary types in his private letters are dealt with. We have tried to put forward Namık Kemal’s contributions on the development of the literary types by dealing with the critics in his private letters under such sub-titles as poetry, drama (theatre) and newspaper. Key Words: Namık Kemal, letters Tanzimat, criticism, poetry, rhyme, thema, metre, theatre, newspape
A criticism on the literary types such as “poetry/ theatre/ newspaper” in Namık Kemal’s letters
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Namık Kemal; Mektup; Tanzimat; Tenkit; Şiir; Kafiye; Tema; Vezin; Tiyatro; Gazete